Web Analytics Tools: Analysis, Perception and Trends - Ionut TANASE; Bianca-Cristiana VOICU; Gheorghe ORZAN (Communications of International Proceedings, 2021)
Since the early days of the internet, the need to measure and analyse web traffic proved to be essential in website and business growth. With an increasing number of web users, organisations needed strong web analytics tools and skills to monitor and to optimise the website performance since each individual visitor brought their own set of data that had to be collected, measured, analyzed and reported. Along with the internet, web analytics tools have developed at a very fast pace over the years, many focusing on analysing different types of data while others on the methods used to collect it. In this article, we have analysed different types of web analytics types and metrics in order to determine their usability among IT teams and organisations.
Keywords: Web Analytics; Web Analytics Tools; Web Analysis Metrics